Sign Language Interpreting in Ireland - Leeson, Lorraine; Lynch, Teresa; Sheridan, Sarah (Gallaudet University Press, 2025)
This chapter documents the development of sign language interpreting (SLI) education and research in Ireland. In 1994, the first cohort of interpreters graduated with a Diploma in Irish Sign Language (ISL)/English Interpreting . The funding for this initial training was provided by the European Union. State funding commenced in 2001, marking the establishment of the Centre for Deaf Studies (CDS) at Trinity College Dublin (TCD). These landmark outcomes were the result of sustained lobbying by the Irish deaf community and allies. As we will see, there were a number of intermittent steps which led to the formation of the CDS, including increased levels of societal and political awareness of ISL and recognition of the Irish deaf community.
Sign language translation and interpreting education two decades on
PUBLISHED
Washington DC
Keywords: Inclusive Society; Making Ireland; Deaf Studies; Irish Sign Language; Irish Sign Language Interpreting; LINGUISTICS; Second language acquisition; interpreting studies; modality and language; Sensory impairment; Deaf/Deafness